Disclinations in C60 molecular layers on WO2/ W(110) surfaces - SHVETS, IGOR (My University, 2014)
A scanning tunneling microscopy study of a planar close-packed C 60 hexagonal molecular layer on a WO 2 / W(110) substrate reveals the existence of C 60 domains exhibiting two preferred orientations at an angle with an underlying periodic groove structure in the substrate. An analysis of the van der Waals interactions between substrate and layer retrieves the observed misorientations as those corresponding to minima in the interaction energy of the substrate-layer system. The misorientation between two C 60 domains is accommodated in a tilt boundary by a linear array of molecular structural units identified as disclination dipoles, i.e., rotational defects in the hexagonal structure of the layer. A field theory of disclinations and dislocations is used to construct maps of the elastic energy, strains, curvatures, and stresses induced by the lattice defects over the layer. The predicted regions of high compression are found to overlap with those where the fullerene molecules do not undergo rotation.
PUBLISHED
Keywords: planar close-packed C; planar close-packed C